The Role of CT Perfusion in Defining the Clinically Relevant Core Infarction to Guide Thrombectomy Selection in Patients with Acute Stroke. Issue 3 (20th January 2019) - Shaker, Hussam; Khan, Muhib; Mulderink, Todd; Koehler, Tracy J.; Scurek, Raymond; Tubergen, Tricia; Packard, Laurel; Singer, Justin; Mazaris, Paul; Min, Jiangyong; Wees, Nabil; Khan, Nadeem; et al.
ABSTRACT: BACKGROUND AND PURPOSE: Infarct core assessment on presentation is important to evaluate salvageable tissue to select patients for thrombectomy. Our study aims to evaluate the correlation between infarct core volume measured by computed tomography (CT) perfusion (CTP) and magnetic resonance diffusion‐weighted imaging (MR‐DWI) in patients with acute large‐vessel occlusion. METHODS: We studied patients who underwent CTP on presentation to the emergency department for stroke symptoms. National Institute of Health Stroke Scale (NIHSS), collateral status, symptomatic vessels, and modified Rankin scale (mRS) at 90 days were collected. Admission infarct core volume was measured on initial relative cerebral blood volume and final infarct core volume on follow‐up DWI. The correlation between two measures was assessed using Pearson's correlation coefficient. RESULTS: Seventy‐four patients were studied of which 41.9% were female. Median NIHSS was 13 (2‐30). Middle cerebral artery occlusion was present in 53 (71.6%) patients and 54 (72.9%) had good collaterals. Good functional outcome of mRS 0‐2 was achieved by 60.8% at 90 days. There was a strong correlation between CTP and MR‐DWI ( r = .94). There was no significant difference between volume (in milliliters) on CTP (54.1 ± 69.8) and volume on DWI (50.3 ± 59.7; P = .18) using the paired t ‐test. CONCLUSION: CTP provides a good estimation of the core infarct volume. It performs well within the clinically relevant thresholds for patient selection for thrombectomy.